2020
DOI: 10.1088/1757-899x/753/6/062021
|View full text |Cite
|
Sign up to set email alerts
|

Management Decision-Making by the Head of the Peasant Farm Enterprise under Conditions of Uncertainty

Abstract: The article considers the uncertainty as one of the risk-forming factors of peasant farm enterprises, identifies the reasons for uncertainty in business activity, considers the trends of small business in agriculture of Irkutsk region, marks out one of the methods of management decision-making under conditions of uncertainty for the peasant (farmer) economy, considers the performance indicators of the peasant farm of Irkutsk region in dynamics, reveals the main problems consisting of worn-out equipment and lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Analysis of the practice of designing mining enterprises in conditions of uncertainty [2] showed that the procedure for substantiating design solutions and parameters of technological systems of coal mining should be approached from the standpoint of intelligent integrated methodologies. The article [3] considers uncertainty as one of the risk factors for the functioning of peasant farms, considers the tendencies of the development of small business in agriculture and suggests options for making managerial decisions to improve their efficiency; transformational changes in the agricultural sector in the context of institutional transformations are disclosed in [4]; the authors of [5] propose a methodological approach to assessing investments that support the economic development of agricultural enterprises in an uncertain competitive environment.…”
Section: Theorymentioning
confidence: 99%
“…Analysis of the practice of designing mining enterprises in conditions of uncertainty [2] showed that the procedure for substantiating design solutions and parameters of technological systems of coal mining should be approached from the standpoint of intelligent integrated methodologies. The article [3] considers uncertainty as one of the risk factors for the functioning of peasant farms, considers the tendencies of the development of small business in agriculture and suggests options for making managerial decisions to improve their efficiency; transformational changes in the agricultural sector in the context of institutional transformations are disclosed in [4]; the authors of [5] propose a methodological approach to assessing investments that support the economic development of agricultural enterprises in an uncertain competitive environment.…”
Section: Theorymentioning
confidence: 99%